2022
DOI: 10.1007/s00330-022-08568-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic CT for the planning of MR-HIFU treatment of bone metastases in pelvic and femoral bones: a feasibility study

Abstract: Objectives Visualization of the bone distribution is an important prerequisite for MRI-guided high-intensity focused ultrasound (MRI-HIFU) treatment planning of bone metastases. In this context, we evaluated MRI-based synthetic CT (sCT) imaging for the visualization of cortical bone. Methods MR and CT images of nine patients with pelvic and femoral metastases were retrospectively analyzed in this study. The metastatic lesions were osteolytic, osteoblastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…While not previously tested in the spine in patients with axSpA, the MRI-based sCT method has been clinically validated in the cervical spine,30 the lumbar spine for surgical planning,31 and in the hip and SIJs 22 31–35. Morbée et al have reported equivalency of sCT to conventional CT regarding geometrical measurements when quantitively assessing bony morphology of the lumbar spine 31.…”
Section: Discussionmentioning
confidence: 99%
“…While not previously tested in the spine in patients with axSpA, the MRI-based sCT method has been clinically validated in the cervical spine,30 the lumbar spine for surgical planning,31 and in the hip and SIJs 22 31–35. Morbée et al have reported equivalency of sCT to conventional CT regarding geometrical measurements when quantitively assessing bony morphology of the lumbar spine 31.…”
Section: Discussionmentioning
confidence: 99%
“…All anatomical characteristics were determined based on the sCT images, and dynamic multiplanar reconstruction (available as a tool in PACS) was allowed. No paired CT data were used as this imaging technique has been clinically validated by several previous studies [13][14][15][16][17][18][19].…”
Section: Image Analysismentioning
confidence: 99%
“…Moreover, these sCT images allow for postprocessing with multiplanar reconstruction, which is practical and useful when examining the complex anatomical structure of the SIJ. This technique has been clinically validated in the SIJ, hips, lumbar spine and cervical spine [13][14][15][16][17][18][19]. In a recent study by Jans et al [14], sCT outperformed T1-weighted MRI images for detection of erosions, sclerosis, and ankylosis of the SIJ in patients with axial spondyloarthritis (axSpA), with reliability comparable to that of CT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fewer studies applied deep learning methods of synthetic CT generation specifically to musculoskeletal disorders. Nevertheless, some studies showed high agreement between synthetic images generated by deep learning and CT, including in the evaluation of morphologic parameters of the hip, 119 surgical planning of the lumbar spine, 120,121 creation of 3D printed models for surgical planning, 122 detection of structural lesions in the sacroiliac joints, 123 and in the treatment planning of bone metastasis by MRI-guided high-intensity focused ultrasound 124 …”
Section: Ai To Create Synthetic Ct From Mrimentioning
confidence: 99%